2002
DOI: 10.1080/00498250210144857
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of selegiline N -oxide, a new indicator for selegiline administration in man

Abstract: 1. The metabolism of selegiline (SG) has been studied by investigating the time-course of urinary excretion of SG and its metabolites using high-performance liquid chromatography-electrospray ionization mass spectrometry (LC-ESI MS) in combination with solid-phase extraction. 2. The excretion profiles of SG and its four major metabolites, selegiline-N-oxide (SGO), N-desmethylselegiline (DM-SG), methamphetamine (MA) and amphetamine (AP), were investigated in six healthy volunteers after oral administrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 15 publications
(19 reference statements)
2
24
0
Order By: Relevance
“…Especially, because N-oxide metabolites readily degrade, as mentioned above, it is well known that N-oxides are normally undetectable by GC/MS. Thus, we concluded that the detection of "NЈ-oxide" (it should be named "hydroxylamine," rather than "NЈ-oxide") in their reports required reexamination by LC/MS, based on our previous studies that dealt with N-oxide metabolites of several other drugs (Katagi et al, 2000(Katagi et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, because N-oxide metabolites readily degrade, as mentioned above, it is well known that N-oxides are normally undetectable by GC/MS. Thus, we concluded that the detection of "NЈ-oxide" (it should be named "hydroxylamine," rather than "NЈ-oxide") in their reports required reexamination by LC/MS, based on our previous studies that dealt with N-oxide metabolites of several other drugs (Katagi et al, 2000(Katagi et al, , 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the generation of another metabolite, deprenyl-N-oxide by flavincontaining monooxygenase (FMO) was proposed by Wu et al [26]. This compound was later identified in vitro in microsomal preparation (from F. Lévai et al, submitted) and in vivo in human urine [27,28]. The metabolic pathways of R-(2)-deprenyl are shown in Fig.…”
Section: Introductionmentioning
confidence: 94%
“…Less selegiline-NOs were 106.85 4 : Formation of selegiline-N-oxide in rat microsomal preparation in vitro in the presence of specific isoenzyme inhibitors metabolites, numerous minor metabolites, such as phydroxydesmethylselegiline, p-hydroxymethamphetamine, p-hydroxyamphetamine, ephedrine, norephedrine, pseudoephedrine, norpseudoephedrine and phenylacetone have been identified in man and/or in various animal species (17). The formation of selegiline-NO as a metabolite of selegiline has previously been postulated (25,34) and it was recently identified in human urine (35,36).…”
Section: Resultsmentioning
confidence: 99%